2013
DOI: 10.1177/1473325013507472
|View full text |Cite
|
Sign up to set email alerts
|

Shifting practices of recovery under community mental health reform: A street-level organizational ethnography

Abstract: This article is part of a larger ethnographic study that seeks to understand how community mental health practice has changed over time in response to shifts in Medicaid management and financing. In this article, I examine the struggle that took place on the ground in one emblematic community mental health agency as frontline workers strived to realize their 'recovery' vision under emerging managerial arrangements of fee-forservice billing. This study finds that managerial reforms conflict with locally forged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Increasingly, states are seeking to "maximize" Medicaid as a mechanism for funding mental health services ( V. K. Smith, Ellis, & Hogan, 1999). Driven largely by federal financial participation incentives, this trend restructures both how mental health needs are defined and what workers must demonstrate as a condition of payment ( Ganju, 2006;Spitzmueller, 2014). Medical necessity guidelines limit the scope of eligibility to activities that are reasonable and necessary based on evidencebased clinical standards of treatment, replacing social models of care with the medical model ( Hoy, 2008).…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Increasingly, states are seeking to "maximize" Medicaid as a mechanism for funding mental health services ( V. K. Smith, Ellis, & Hogan, 1999). Driven largely by federal financial participation incentives, this trend restructures both how mental health needs are defined and what workers must demonstrate as a condition of payment ( Ganju, 2006;Spitzmueller, 2014). Medical necessity guidelines limit the scope of eligibility to activities that are reasonable and necessary based on evidencebased clinical standards of treatment, replacing social models of care with the medical model ( Hoy, 2008).…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…Two years from receipt of funding, and 1 year since accepting the first client, we found NBMPIR had devoted much time to the governance and management of the Consortium and to establishing a reporting framework. Conflict both within and across organisations is described in the literature as an impediment for effective recovery based service provision [15, 55] that is addressed by clarifying roles and expectations [15]. To this end NBMPIR signed Memoranda of Understanding and Service Level Agreements with all Consortium service provider partners.…”
Section: Discussionmentioning
confidence: 99%
“…These approaches are recommended to include recovery-based, consumer-driven, locally specific approaches focussed on empowerment [1013], and coordination and integration of the multiple services required to meet consumer needs [5, 14]. However, barriers to recovery based care models have been identified including management conflicts [15], difficulties accurately measuring consumer and system outcomes [5, 10, 12, 14] and need for a commonly understood conceptual framework to guide practice [10, 12, 16], challenging the expertise of service providers [12, 17], and failure to value the experiences of street level workers [15, 18] and consumers [16, 19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…Focus groups conducted with mental health providers in the United Kingdom found that staff viewed funding priorities of the National Health System as “competing” with the priorities of recovery (LeBoutiller, et al, 2015). An ethnographic study of street-level practice in a community mental health clubhouse in the United States noted several “unresolvable contradictions” between funder requirements and local practices when the program underwent a transition from block grant funding to a fee-for-service payment model (Spitzmueller, 2013; Spitzmueller, 2016). The focus of these financial reforms (cost-efficiency, accountability, and standardization) fundamentally came into conflict with the clubhouse model’s promotion of consumer self-determination and program responsiveness, which impacted workers’ perceptions of problem clients, altered their conceptions of the work role, and increased service rationing.…”
Section: Introductionmentioning
confidence: 99%